Pregunta
(2) In each of the following expren of other variables; write \( z \) in terms of \( 2.1 x=\sqrt{z+y} \) \( 2.2 x=\frac{\text { abcz }}{3} \) \( 2.3 a=b-3 z \) \( 2.4 y=\frac{\sqrt{z}}{5} \) \( 2.6 y=\frac{3-2 z}{x+z}-1 \) \( 2.5 x=\frac{3 z+m}{2}-1 \)
Ask by Lindsey Marsh. in South Africa
Feb 04,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
Here are the values of \( z \) in terms of the other variables:
1. \( z = x^2 - y \)
2. \( z = \frac{3x}{\text{abc}} \)
3. \( z = \frac{b - a}{3} \)
4. \( z = 25y^2 \)
5. \( z = \frac{2x + 2 - m}{3} \)
6. \( z = \frac{3 - x(y + 1)}{y + 3} \)
Solución
Sure, let's solve each equation for \( z \) in terms of the other variables.
---
### **2.1** \( x = \sqrt{z + y} \)
**Solution:**
1. Square both sides to eliminate the square root:
\[
x^2 = z + y
\]
2. Solve for \( z \):
\[
z = x^2 - y
\]
**Answer:**
\[
z = x^2 - y
\]
---
### **2.2** \( x = \frac{\text{abcz}}{3} \)
**Solution:**
1. Multiply both sides by 3 to isolate \( \text{abcz} \):
\[
3x = \text{abcz}
\]
2. Divide both sides by \( \text{abc} \) (assuming \( \text{abc} \neq 0 \)):
\[
z = \frac{3x}{\text{abc}}
\]
**Answer:**
\[
z = \frac{3x}{\text{abc}}
\]
---
### **2.3** \( a = b - 3z \)
**Solution:**
1. Subtract \( b \) from both sides:
\[
a - b = -3z
\]
2. Divide both sides by \( -3 \):
\[
z = \frac{b - a}{3}
\]
**Answer:**
\[
z = \frac{b - a}{3}
\]
---
### **2.4** \( y = \frac{\sqrt{z}}{5} \)
**Solution:**
1. Multiply both sides by 5:
\[
5y = \sqrt{z}
\]
2. Square both sides to eliminate the square root:
\[
25y^2 = z
\]
**Answer:**
\[
z = 25y^2
\]
---
### **2.5** \( x = \frac{3z + m}{2} - 1 \)
**Solution:**
1. Add 1 to both sides:
\[
x + 1 = \frac{3z + m}{2}
\]
2. Multiply both sides by 2:
\[
2(x + 1) = 3z + m
\]
3. Subtract \( m \) from both sides:
\[
2x + 2 - m = 3z
\]
4. Divide both sides by 3:
\[
z = \frac{2x + 2 - m}{3}
\]
**Answer:**
\[
z = \frac{2x + 2 - m}{3}
\]
---
### **2.6** \( y = \frac{3 - 2z}{x + z} - 1 \)
**Solution:**
1. Add 1 to both sides:
\[
y + 1 = \frac{3 - 2z}{x + z}
\]
2. Multiply both sides by \( x + z \):
\[
(y + 1)(x + z) = 3 - 2z
\]
3. Expand the left side:
\[
yx + y z + x + z = 3 - 2z
\]
4. Collect like terms involving \( z \):
\[
z(y + 1) + 2z = 3 - yx - x
\]
5. Factor out \( z \):
\[
z(y + 3) = 3 - x(y + 1)
\]
6. Divide both sides by \( y + 3 \) (assuming \( y + 3 \neq 0 \)):
\[
z = \frac{3 - x(y + 1)}{y + 3}
\]
**Answer:**
\[
z = \frac{3 - x(y + 1)}{y + 3}
\]
---
Feel free to reach out if you have any further questions!
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
The Deep Dive
For \( 2.1 \), to express \( z \) in terms of \( x \) and \( y \), we rearrange the equation: \( x = \sqrt{z + y} \). Squaring both sides gives us \( x^2 = z + y \), so \( z = x^2 - y \). In \( 2.2 \), we want to isolate \( z \). Starting from the equation \( x = \frac{\text{abcz}}{3} \), we can rearrange it to \( z = \frac{3x}{abc} \). Voilà, \( z \) is expressed in terms of \( x \), \( a \), \( b \), and \( c \)!
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium